An Examination of “Rationality’’ on President George Bush (Jr) Second Gulf War Intelligence - Bodunde, David Oluwafemi (Journal of Contemporary International Relations and Diplomacy, 2022)
The world is faced with a series of security problems and the need to address such problems depends on the leaders at the helm of affairs. International problems such as the threat of terrorism, Weapons of Mass Destruction cannot be treated with levity, they require deep thinking with a rational mind to prevent or cause war. However, the issue of leadership committing his nation to war or not is been addressed within the corridor of exercise of power. Critical case of the second Gulf war had questioned the rationality of President George Bush (Jnr) in prosecuting the war despite opinion polls that were against it. Since the war attracted political and academic debate bothering on rationality, it is worthwhile to attempt this paper by examining President George Bush’s (Jnr) rationality or otherwise in going for the war. The paper is based on qualitative analysis with the application of textbooks, journals, periodicals, and adopted interviews published on the websites. It also concluded that rationality is a beauty in the eye of the beholder and that American foreign policies are the instruments that any of its leaders must follow to achieve national interest based on primacy, democratic philosophy, and a world order based on his degree of rationality.